2001
DOI: 10.1021/ma991897r
|View full text |Cite
|
Sign up to set email alerts
|

Chain Conformation and Crystallization Behavior of the Syndiotactic Polystyrene Nanocomposites Studied Using Fourier Transform Infrared Analysis

Abstract: Analyses of the effects of montmorillonite (clay) on the chain conformation and crystallization of syndiotactic polystyrene (s-PS) thin films are investigated using FTIR spectroscopy, X-ray diffraction, and TEM. The clay is dispersed into the s-PS matrix using a solution blending with scale in 1−2 nm or in a few tenths to 100 nm, depending on whether a surfactant is added or not. Upon adding clay, the chain conformation of s-PS tends to convert to TTTT from TTGG after drying because the highly dispersed clay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…In this paper, we describe the preparation of two types of nanocomposites formed from clays treated with either cetylpyridinium chloride (CPC) or the CPC/a-CD inclusion complex. The PS/clay nanocomposite formed using the CPC-treated clay exhibited no significant improvements in its thermal properties [23][24][25][26][27]. We found that CPC, a linear aliphatic surfactant, is able to form a crystalline complex with cyclodextrin.…”
Section: Introductionmentioning
confidence: 76%
“…In this paper, we describe the preparation of two types of nanocomposites formed from clays treated with either cetylpyridinium chloride (CPC) or the CPC/a-CD inclusion complex. The PS/clay nanocomposite formed using the CPC-treated clay exhibited no significant improvements in its thermal properties [23][24][25][26][27]. We found that CPC, a linear aliphatic surfactant, is able to form a crystalline complex with cyclodextrin.…”
Section: Introductionmentioning
confidence: 76%
“…Confinement effects are well known and have been described elsewhere. [14][15][16] Significant alterations in crystallite morphology [11,13,[17][18][19][20][21][22][23][24][25][26] and orientation, [11,13,17,18,21,24,[26][27][28] as well as the crystalline phase(s) present, [11,13,21,[26][27][28][29][30][31][32][33][34][35][36] will also affect the materials properties. Finally, the flexible nature of these layers [37] and their propensity to align at high strains [11,13,[26][27][28][38][39][40][41] and to induce void formation at high stresses [17,…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings on the polymorphism issue demonstrated that addition of foreign particles (clays [30,31] and nano-CaCO 3 [29]) or miscible polymers (aPS [32], poly(styrene-co-a-methyl styrene [33], and poly(2,6-dimethylphenylene) [32,34]) seem to favor the b-form and depress the a-form formation.…”
Section: Cnc Effects On the Crystal Modification Of Spsmentioning
confidence: 99%